Biblioterapi i ett litteraturvetenskapligt perspektiv - Pettersson, Cecilia (Tidskrift för litteraturvetenskap, 2014)
Bibliotherapy from a Literary Perspective This article aims to introduce and discuss the phenomenon of bibliotherapy in the context of comparative literature in Sweden. It opens with an introduction to the field of bibliotheraphy, defining this as the use of books to aid people in their healing processes. The article discusses this definition, and provides a short historical overview of the treatment of bibliotheraphy, placing particular focus on ”interactive” bibliotheraphy which, in many respects, has become the model of bibliotherapeutic intervention today. Primarily, however, this article explores how a literary perspective could contribute to the research on bibliotheraphy. Firstly, I consider a variety of different studies and their views on bibliotheraphy in order to make clear the values and the perspectives on literature underpinning much of the research in the field. Secondly, I examine the different conceptions of the reader and the reading process expressed in the research on bibliotheraphy in relation to reader-response criticism. Among other things, the model of the bibliotherapeutical reading process used in the school of interactive bibliotheraphy is discussed. This model is shown to be highly normative when it comes to how one can read in order to be aided in the healing process. In conclusion, the article raises questions concerning how other views on bibliotheraphy might produce alternative models of reading.